MPEA´s ostomy nursing research wins the 1st prize - Isabel CF da Cruz (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
II Brazilian Congress of Stomatotherapy Researchs promoted by the Brazilian Stomatotherapy Society gave the First Prize to Vera Perissé, graduate student in Professional Master in Nursing Program/Fluminense Federal University, who lead the research related to families of clients with gastrostomy along with her advisor: Dra. Fátima Helena. The award was presented on May 25th during the Congress. This award is so important for the MPEA because it confirms that high-quality scientific research for professional problems goes hand in hand with high-quality university education